(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of this study was to investigate the impact of academic Leaders (deans and department heads) leadership style on academic staffs job satisfaction in Ethiopian Public universities. The study employed descriptive survey method and used quantitative approach. Deans, Department heads and academic staffs were source of data. Participants were selecting using simple random sampling method. LEAD-others, Demographic Variables Survey questionnaires and Job Satisfaction Survey were employed to collect data. Mean, standard deviation, ANOVA and post hoc were used as analysis tool. The result of this study showed that the highest job satisfaction was observed for participating leadership style followed by delegating and selling whereas the least job satisfaction was observed for telling leadership style even though job satisfaction of academic staffs’ were observed greater than the expected mean. Hence, the study was focused on leadership style and job satisfaction of academic staff, to confidently determine whether leaders are employing the right leadership style, one need to know the ability and maturity level of the followers. So my strong recommendation to further studies is to investigate both followers maturity level and leadership style in higher education institution context. Furthermore, it is also advisable that the universities to arrange valuable trainings for academic leaders (deans and department heads) to make them capable of varying their leadership styles to fit into situations.